Asymmetrical canina meiosis is accompanied by the expansion of a pericentromeric satellite in non-recombining univalent chromosomes in the genus Rosa - Lunerová, Jana; Herklotz, Veit; Laudien, Melanie; Vozárová, Radka; Groth, Marco; Kovařík, Aleš; Ritz, Christiane M (Annals of botany, 2020)
BACKGROUND AND AIMS: Despite their abundant odd-ploidy (2n = 5x = 35), dogroses (Rosa sect. Caninae) are capable of sexual reproduction due to their unique meiosis. During canina meiosis, two sets of chromosomes form bivalents and are transmitted by male and female gametes, whereas the remaining chromosomes form univalents and are exclusively transmitted by the egg cells. Thus, the evolution of chromosomes is expected to be driven by their behaviour during meiosis. METHODS: To gain insight into differential chromosome evolution, fluorescence in situ hybridization was conducted for mitotic and meiotic chromosomes in four dogroses (two subsections) using satellite and ribosomal DNA probes. By exploiting high-throughput sequencing data, we determined the abundance and diversity of the satellite repeats in the genus Rosa by analysing 20 pentaploid, tetraploid and diploid species in total. KEY RESULTS: A pericentromeric satellite repeat, CANR4, was found in all members of the genus Rosa, including the basal subgenera Hulthemia and Hesperhodos. The satellite was distributed across multiple chromosomes (5-20 sites per mitotic cell), and its genomic abundance was higher in pentaploid dogroses (2.3 %) than in non-dogrose species (1.3 %). In dogrose meiosis, univalent chromosomes were markedly enriched in CANR4 repeats based on both the number and the intensity of the signals compared to bivalent-forming chromosomes. Single-nucleotide polymorphisms and cluster analysis revealed high intragenomic homogeneity of the satellite in dogrose genomes. CONCLUSIONS: The CANR4 satellite arose early in the evolution of the genus Rosa. Its high content and extraordinary homogeneity in dogrose genomes is explained by its recent amplification in non-recombining chromosomes. We hypothesize that satellite DNA expansion may contribute to the divergence of univalent chromosomes in Rosa species with non-symmetrical meiosis.
Keywords: polyploidy; Genome, Plant; genom rostlinný; hybridizace in situ fluorescenční; genetic recombination; Rosa; chromosome evolution; Meiosis; meiosis; dogroses; DNA rostlinná; DNA, Plant; meióza; lidé; Humans; In Situ Hybridization, Fluorescence; repeatome; Polyploidy; satellite DNA; polyploidie